Hypersonic nonequilibrium flows : fundamentals and recent advances - Josyula, Eswar (American Institute of Aeronautics and Astronautics, 2015)
This book provides an overview of the recent developments in precision aerial cargo delivery from the standpoint of developing guidance, navigation and control (GNC) algorithms for the self-guided parafoil and parachute-based aerial delivery systems (PADS). Developing a robust GNC system involves aerodynamics modeling, structural and parametric system identification, understanding the environment PADS glides through developing and testing suitable navigation solutions, guidance strategies, and controllers. -- Provided by publisher.
"Hypersonic nonequilibrium flows includes fundamental governing equations of nonequilibrium fluid transport and computational approach to calculation of rates and cross-sections in quantized energy states; Direct Simulation Monte Carlo (DSMC) approach; radiative heat transfer; a Computational Fluid Dynamics (CFD) perspective; surface chemistry, with additional chapters on high enthalpy facilities and the associated diagnostic techniques."--Publisher description
Keywords: Aerodynamics, Hypersonic.; Nonequilibrium thermodynamics.; Enthalpy.; elektronické knihy; electronic books